On the status of Helicops wettsteini Amaral, 1929, a senior synonym of Hypsiscopus murphyi (SERPENTES: Homalopsidae) - David, Patrick; Vogel, Gernot (Zootaxa, 2024)
We redescribe the name-bearing types of Helicops wettsteini Amaral, 1929, a species described from central Costa Rica. However, while Helicops wettsteini has been considered in the literature a synonym of Hypsiscopus plumbeus (previously Enhydris plumbea), we present here morphological evidence for considering Helicops wettsteini a synonym of the recently described species Hypsiscopus murphyi Bernstein, Voris, Stuart, Phimmachak, Seateun, Sivongxay, Neang, Karns, Andrews, Osterhage, Phipps & Ruane, 2022, which hence becomes a junior subjective synonym of Hypsiscopus wettsteini (Amaral, 1929).